Reprogramming adult cells during organ regeneration in forest species - Abarca, Dolores (Landes Bioscience, 2009)
The possibility of regenerating whole plants from somatic differentiated cells emphasizes the plasticity of plant development. Cell-type respecification during regeneration can be induced in adult tissues as a consequence of injuries, changes in external or internal stimuli or changes in positional information. However, in many plant species, switching the developmental program of adult cells prior to organ regeneration is difficult, especially in forest species. Besides its impact on forest productivity, basic information on the flexibility of cell differentiation is necessary for a comprehensive understanding of the epigenetic control of cell differentiation and plant development. Studies of reprogramming adult cells in terms of regulative expression changes of selected genes will be of great interest to unveil basic mechanisms regulating cellular plasticity.